A Systematic Review of Paired Associative Stimulation (PAS) to Modulate Lower Limb Corticomotor Excitability: Implications for Stimulation Parameter Selection and Experimental Design - Alder, Gemma; Signal, Nada; Olsen, Sharon; Taylor, Denise (Frontiers in Neuroscience, 2019)
Non-invasive neuromodulatory interventions have the potential to influence neural plasticity and augment motor rehabilitation in people with stroke. Paired associative stimulation (PAS) involves the repeated pairing of single pulses of electrical stimulation to a peripheral nerve and single pulses of transcranial magnetic stimulation over the contralateral primary motor cortex. The efficacy of PAS in the lower limb of healthy and stroke populations has not been systematically appraised, and optimal protocols, including stimulation parameter settings, have yet to be determined. This systematic review evaluates: a) the efficacy of PAS on lower limb corticomotor excitability in healthy and stroke populations, and b) the stimulation parameters employed. Five databases were searched for randomised, non-randomised, and pre-post experimental studies, that investigated the efficacy of lower limb PAS in healthy and stroke populations. Two independent reviewers identified eligible studies and assessed methodological quality using the modified Downs and Blacks Tool and the TMS Checklist. PAS stimulation parameters and TMS measurement methods were also extracted and compared. Twelve articles, comprising 24 experiments, met the inclusion criteria. Four articles evaluated PAS in people with stroke. Following a single session of PAS, 21 experiments reported modulation of corticomotor excitability, lasting up to 60 minutes; however, the research lacked methodological rigour. Intervention stimulation parameters were highly variable across experiments, and whilst these appeared to influence efficacy, variations in the intervention and outcome assessment methods hindered the ability to draw conclusions about optimal parameters. Lower limb PAS requires further investigation before considering its translation into clinical practice. Eight key recommendations are offered as a guide for enhancing future research in the field.